Experimental Study on Structural Performance of Cast-in-Place Frame Printed Concrete Wall - Yanan Fu; Ying Zhang; Lei Wu (International Journal of Concrete Structures and Materials, 2023)
Abstract A growing number of nations and regions have printed concrete structures thanks to the application of 3D printing technology in the field of civil engineering. However, the houses built with printed concrete are mostly printed concrete wall structures with composite load-bearing walls and cast-in-place frames. This structure solely takes into account the performance of the structure under vertical loads, which does not address its ability to withstand horizontal loads. In this paper, wall specimens were designed and tested under horizontal reciprocal loads in order to investigate the structural performance of this cast-in-place border-frame printed concrete wall structure under horizontal loads. Four factors are examined in order to determine how well the cast-in-place frame printed concrete wall structure performs when subjected to horizontal loads: column longitudinal reinforcement strain, hysteresis curve, skeleton curve, and energy dissipation capacity. According to the test results, the addition of the wall increased the bearing capacity and accumulated energy dissipation of the specimen, but the increase in stiffness also caused the structural ductility to decrease. As a result, cracks were more likely to generate at the wall–column joints, so the stiffness matching between the printed concrete wall and the cast-in-place side frame needed to be further coordinated to obtain a higher ductility. It turns out that the wall sections have little impact on the seismic performance of the members.